2021
DOI: 10.1021/acscatal.0c04768
|View full text |Cite
|
Sign up to set email alerts
|

Metal Bound or Free Ylides as Reaction Intermediates in Metal-Catalyzed [2,3]-Sigmatropic Rearrangements? It Depends

Abstract: Density functional theory calculations were applied to study four previously published metalcatalyzed [2,3]-rearrangements from onium ylide intermediates, in pursuit of generalizations about when, during these types of reactions, catalysts dissociate. Our results corroborate past studies where free ylide mechanisms were proposed to be operative. Calculations on case studies predict that the origin of metal-catalyst 'falling off' (dissociation) can be attributed primarily to the steric bulkiness of functional g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 102 publications
1
24
0
Order By: Relevance
“…By delving into such previously published experimental studies, we set out to (a) confirm that our theoretical approaches could provide results consistent with experiments and (b) determine the physical factors that impact whether metal catalyst remains bound during the rearrangement step, thereby setting the stage for future reaction design. 41 In the four reactions examined, three with Rh and one with Au, we found that our calculations supported the conclusions from control experiments. Here, we utilized the (U)B3LYP/LANL2DZ[6-31G(d)] level of theory to investigate the mechanism (single-point calculations with dispersion correction and with other functionals produced qualitatively similar results).…”
Section: Review Synthesissupporting
confidence: 78%
See 3 more Smart Citations
“…By delving into such previously published experimental studies, we set out to (a) confirm that our theoretical approaches could provide results consistent with experiments and (b) determine the physical factors that impact whether metal catalyst remains bound during the rearrangement step, thereby setting the stage for future reaction design. 41 In the four reactions examined, three with Rh and one with Au, we found that our calculations supported the conclusions from control experiments. Here, we utilized the (U)B3LYP/LANL2DZ[6-31G(d)] level of theory to investigate the mechanism (single-point calculations with dispersion correction and with other functionals produced qualitatively similar results).…”
Section: Review Synthesissupporting
confidence: 78%
“…161 In discussing the nature of the oxonium, sulfonium, and selenonium ylides in our study -wherein we found metalbound oxonium ylides and free sulfonium and selenonium ylides -we made the point that our conclusions "should not be generalized to all similar ylides undergoing [2,3]-rearrangements." 41 The work by Dang's group bolsters our observation that the nature of the ylide is system-dependent. Enabled by the work done by experimental (and other computational) groups, we seem to have converged on two key factors that determine whether an ylide intermediate is free or metal-bound: (a) steric bulk directly attached to the carbene carbon 41 and (b) the electronic nature of the heteroatom directly bound to the carbene carbon.…”
Section: Review Synthesismentioning
confidence: 93%
See 2 more Smart Citations
“…The reaction of organoselenium compounds with carbenes constitutes an important transformation to rapidly build‐up molecular complexity via sigmatropic rearrangement reactions [1–7] . In 1995, Uemura initially described the reaction of allyl selenides with aryldiazoacetates in the presence of copper catalysts [3] .…”
Section: Methodsmentioning
confidence: 99%